Guidelines for the diagnosis and management of acute myeloid leukaemia in pregnancy. (17th June 2015) - Ali, Sahra; Jones, Gail L.; Culligan, Dominic J.; Marsden, Philippa J.; Russell, Nigel; Embleton, Nicholas D.; Craddock, Charles; the British Committee for Standards in Haematology
Summary of recommendations Pregnant women should be managed by a multidisciplinary team that includes haematologists, obstetricians, neonatologists and anaesthetists (Grade 1C) As for non‐pregnant patients, acute myeloid leukaemia (AML) should be diagnosed using the World Health Organization (WHO) classification (Grade 1A) Women diagnosed with AML in pregnancy should be treated without delay (Grade 1B) When the diagnosis of AML is made in the first trimester, a successful pregnancy outcome is unlikely and spontaneous pregnancy loss in this situation carries considerable risks for the mother. The reasons for and against elective termination should be discussed with the patient (Grade 2C) In the case of presentation beyond 32 weeks gestation, it may be reasonable to deliver the foetus prior to commencement of chemotherapy (Grade 2C) Between 24 and 32 weeks, risks of foetal chemotherapy exposure must be balanced against risks of prematurity following elective delivery at that stage of gestation (Grade 1C) The risk‐benefit ratio must be carefully considered before using any drugs in pregnancy (Grade 1C) Where AML induction chemotherapy is delivered, a standard daunorubicin, cytarabine 3 + 10 schedule should be used (Grade 1B) Chemotherapy should be dosed according to actual body weight and adjustments made for weight changes during treatment (Grade 1C) Quinolones, tetracyclines and sulphonamide use should be avoided in pregnancy (Grade 1B) Amphotericin B or lipid derivatives are the antifungal of choice in pregnancy (Grade 2C) Cytomegalovirus (CMV)‐negative blood products should be administered during pregnancy regardless of CMV serostatus (Grade 1B) A course of corticosteroids should be considered if delivery is anticipated between 24 and 35 weeks gestation, given over a 48‐h period during the week prior to delivery (Grade 1A) Use of magnesium sulphate should be considered in the 24 h prior to delivery if this is before 30 weeks gestation (Grade 1A) Where possible, delivery should be planned for a time when the woman is at least 3 weeks post‐chemotherapy to minimize risk of neonatal myelosuppression (Grade 1C) Planned delivery is easier to manage than spontaneous labour; induction of labour is usually advised (Grade 2C) Epidural analgesia should be avoided in a woman who is significantly thrombocytopenic (platelet count <80 × 109/l) and/or neutropenic (white blood cell count <1 × 109/l): (Grade 1C) Elective caesarean section should only be recommended for obstetric indications (Grade 2C) Antibiotics should be administered during and after premature rupture of membranes and delivery (Grade 1C)